Determine the quality and effectiveness of teaching materials of training systems - Данченко, Алла Леонидовна; Ульшин, Виталий Александрович (Eastern-European Journal of Enterprise Technologies, 2010)
The architecture of learning system was dveloped for monitoring of educational materials and structural model of distance course with ranking didactic purposes, a method for determining the quality and effectiveness of taining materials was offered.